جمعية محمد ألامين العمودي وإشعاعها الثقافي بوادي سوف - قشاشطة,جهاد; بلول,سمية; غالية,صبرين (University of Eloued جامعة الوادي, 2024)
The idea of establishing this association dates back to the year 1988, when a group of intellectuals in the state gathered, initiated by the director of the Cultural Center Badi's Kaddara and with the support of the Secretary of the National Liberation Front in Eloued Bouzid Kahoul, to organize an intellectual seminar coinciding with the opening of medium school, Mohamed Al-Amin Al-Amoudi. This initiative was well received and interacted with by all the intellectuals and civil society members who attended, leading to the idea of establishing an association affiliated with the symbol of Mohamed Al-Amin. This was decided in a meeting at the Cultural Center on May 15, 1988, with 43 founding members. The association focused its efforts on the cultural field, seeking to achieve its main goal of revitalizing the cultural life in Wadi Souf through various activities organized at the local level. As a result, its activities expanded to the national and international levels, thanks to the experience gained as a local association. تعود فكرة تأسيس هذه الجمعية الى سنة 1988,عندما اجتمع مجموعة من المثقفين الولاية وبمبادرة من مدير دار الثقافة باديس قدادرة وبدعم من أمين محافظة جبهة التحرير الوطني بالوادي بوزيد كحول على تنظيم ندوة فكرية بالتزامن مع افتتاح متوسطة الصحن الأول محمد الأمين العمودي. فلقيت هذه المبادرة استحسان وتفاعل كل من حضرها من المثقفيين والمجتمع المدني من هنا جاءت فكرة تأسيس جمعية تنتسب الى العلامة محمد الأمين وذلك في اجتماع بدار الثقافة يوم 15ماي1988 وبلغ عدد مؤسسيها 43عضوا ,ركزت جهودها على الميدان الثقافي حيث سعت الى تحقيق اهم هدف لها وهو تنشيط وتحريك الحياة الثقافية بوادي سوف من خلال مختلف النشاطات التي قامت بتنظيمها على مستوى المحلي, وكانت نتيجة ذلك ان انتقلت بنشاطاتها على مستوى الوطني والعالمي بفضل التجربة التي خاضتها كجمعية محلية.
1988-2000م
Keywords: الجمعية الثقافية محمد الأمين العمودي; سعد العمامرة; الندوات الفكرية السنوية; النشاطات الفكرية